Discourse functions of formulaic sequences in academic speech across two disciplines - Hadi Kashiha,; Chan, Swee Heng (Penerbit UKM, 2014)
Formulaic sequences play a crucial role in building academic discourse. From among the variety of formulaic expressions, lexical bundles have been shown to serve particular facilitative functions in academic discourse. Defined as strings of word forms that commonly co-occur in natural discourse, lexical bundles are characterized statistically by their frequency of occurrence and they contribute significantly to fluency in speech and writing. While previous research had focused on the use of these expressions in academic research articles across disciplines or on the difference between spoken and written registers, little research has been carried out to find out the language use of academic lectures from different disciplines in terms of the use of these bundles, orally. Taking into account this consideration, the present study aimed to investigate how lexical bundles are used by academic lecturers from different disciplinary communities. With the aim of comparing their language selection, the most frequent four-word lexical bundles in academic lectures of two disciplines, namely politics and chemistry were identified and categorized. The procedure adopts Biber et al.‟s (2004) functional categorization of lexical bundles to investigate the communicative purposes that lexical bundles convey in the lectures of the two groups and to see whether there were any disciplinary differences with regard to the bundles used. Based on the findings, there were some marked variations found across the two disciplines in terms of discourse functions of the lexical bundles. It seemed that academic lectures rely heavily on the use of specific word combinations to fulfill those functions related to their discipline.